Dabigatran and myocardial infarction: a foggy scenario - Pontillo D; Patruno N (Vascular Health and Risk Management, 2014)
Daniele Pontillo,1 Nicolino Patruno21Division of Cardiology, Hospital Complex Belcolle, Pavilion Montefiascone Montefiascone, Italy; 2Division of Cardiology, San Giuseppe Hospital, Albano Laziale (RM), ItalyThe pooled analysis from Clemens et al1 furnishes an up-to-date contribution on the scenario of the risk of myocardial infarction (MI) of patients on dabigatran in any disease setting, formulating a "non-guilty" sentence in favor of dabigatran in terms of net clinical benefit, even though the authors did find an absolute increase in MIs. We believe that this contribution may represent further evidence favoring the overall efficacy of dabigatran, in agreement with data from Hohnloser et al2 who analyzed the cardiovascular (CV) ischemic outcomes from the RE-LY (Randomized Evaluation of Long-term anticoagulant therapy) study and finding no statistically significant difference of MI between dabigatran and the comparison treatment, and with those from Dans et al3 who considered solely CV mortality with no further discrimination. Essentially, this represents the leitmotif of the last three years after the revised adjudication of cardiovascular events in the RE-LY study4 with a non-significant increase in MIs with dabigatran at any dose (for 150 mg twice a day, relative risk 1.27, 0.94–1.71, P=0.12).View original paper by Clemens and colleagues.